Analysis of the Effect of Mudharabah and Musyarakah Financing on Credit Risk (Non-Performing Financing) in Islamic Commercial Banks for the 2020–2024 Period - Rise Indriyani; Hayatul Millah; Yeni Kartikawati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effect of mudharabah and musyarakah financing on credit risk, as measured by Non-Performing Financing (NPF), in Islamic Commercial Banks in Indonesia during 2020–2024. This study is based on the phenomenon of increased financing with a profit-sharing scheme that does not always follow an increase in credit risk, thus indicating a dynamic relationship between the two variables. This study applies a quantitative method with an associative research type. The data used are secondary data taken from Islamic Banking Statistics published by the Financial Services Authority (OJK). The analytical method used is multiple linear regression after conducting hypothesis testing and classical assumptions such as normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results of this study indicate that mudharabah financing does not have a significant effect on NPF when viewed individually, with a significance value of 0.203. On the other hand, musyarakah financing also shows no significant effect, with a significance value of 0.470. In this case, both mudharabah and musyarakah combined do not have a significant effect on NPF, with a significance level of 0.430. The Adjusted R Square value obtained is 0.230, which indicates that the independent variables in this study are only able to explain 23% of the variation in NPF, while the rest is influenced by other factors outside this study. Based on the results obtained, it can be stated that financing with the mudharabah and musyarakah systems does not have a significant impact on Non-Performing Financing (NPF) throughout the study period.